2011
DOI: 10.1063/1.3587089
|View full text |Cite
|
Sign up to set email alerts
|

Electron streams formation and secondary two stream instability onset in the post-saturation regime of the classical Weibel instability

Abstract: The electrostatic activity in the post-saturation regime of the velocity anisotropy driven Weibel instability is investigated by means of 1D 3V particle in cell simulations. Two different initial simulation configurations have been chosen to characterize the electrostatic activity in the post-saturation stage. A secondary two stream instability arises in both cases. However, significant differences occur in the thickness of the electron streams, in their initial locations, and in their effects on the bulk elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Such an instability is usually referred as the electrostatic two-stream instability as in Ref. 5, which begins with a symmetry-breaking instability of pair-wise merging of holes, …”
Section: B Detailed Phase Space Representation Afforded By the V-modelmentioning
confidence: 99%
“…Such an instability is usually referred as the electrostatic two-stream instability as in Ref. 5, which begins with a symmetry-breaking instability of pair-wise merging of holes, …”
Section: B Detailed Phase Space Representation Afforded By the V-modelmentioning
confidence: 99%
“…The numerical results of the nonlinear Vlasov simulation not only show that the saturation is governed by strong magnetic trapping, as expected, but evidence that the concept of 'stream' is important in WI. As already indicated in Lemons, Winske & Gary (1979), Innocenti et al (2011) and Inglebert et al (2012), these particle streams are connected to the property of invariance of the canonical momentum in the perpendicular direction and allow to provide a physical picture of WI.…”
Section: 33mentioning
confidence: 99%
“…The idea to highlight such magnetic trapping structures was already be considered by Innocenti et al (2011) using PIC simulations. In the semi-Lagrangian model, the code is accurate enough to exhibit locally such trapping structures without any smoothing technique.…”
Section: Simulations Based On the Multi-stream Modelmentioning
confidence: 99%
“…by the self-generated magnetic field, leads to the formation of local bumps and thus to the set up of a secondary bump on tail instability responsible for the growth of resonant electrostatic modes (ESs) on scales now smaller than the instability length scale. 4 More recently, using a Hamiltonian description of particle motion and 1D3V PIC simulation, Innocenti et al 7 in a similar regime have identified the role of such electrostatic activity as a result of "a two-stream" like instability, leading to the formation of phase space electron holes. These 1D3V PIC simulations show that the Hamiltonian description of particle motion in the 1D limit is a valuable tool to understand the plasma dynamics as described in terms of particle bunches, each bunch having the same perpendicular canonical momentum.…”
Section: Introductionmentioning
confidence: 99%